Evaluation of innovative agricultural extension projects using novel investment tools - Michailidis, Anastasios; Chatzitheodoridis, Fotios; Theodosiou, George (Technological and Economic Development of Economy, 2010)
This article extends the employment of novel investment evaluation tools into agricultural extension issues. In particular the concept of real options methodology has modulated, into an innovative agricultural project called “wema”, to model design flexibility in the realistically uncertain environment of information and communication technologies (ICT). Taking into account the great importance of ICTs, as the principal driver of change in agricultural areas, as well as the drastic increase in ICTs adoption over the last decade, a study evaluating the adoption parameters of ICTs can prove significantly valuable. Besides, any issue related to ICTs is extremely interesting and it belongs to the modern subject‐matters of the agricultural economics science. Empirical results revealed that, according to the traditional criterion (Net Present Value), the implementation plan of the “wema” project is feasible. However, assuming the presence of uncertainty, application of a real options approach demonstrates that the Net Present Value may lead stakeholders to faulty decisions, as the innovative plan is rejected. The results indicate that the options have a significant value and highlight the fact that ignoring options value process can lead to a significant error. This obviously indicates the importance of combining the Net Present Value criterion in agricultural extension investments with the real options approach. Article in English. Inovacinių žemės ūkio plėtros projektų vertinimas naujomis investicinėmis priemonėmis Santrauka. Straipsnyje aprašomos naujos investavimo į žemes ūkio plėtrą vertinimo priemonės. Sukurta realių alternatyvų metodologija, kuri pritaikyta inovatyviame “Wema” žemes ūkio projekte. Empiriniai rezultatai atskleidė, kad pagal tradicinį kriterijų – grynąją dabartine verte – “Wema” projektą įgyvendinti įmanoma. Tačiau projekto dalyviai, šiuo metodu vertindami neapibrežtumus, gali priimti klaidingą sprendimą ir projektą atmesti. Tai akivaizdžiai rodo, kad vertinant žemes ūkio pletros projektus, grynosios dabartines vertės kriterijų reikia derinti su realių alternatyvų metodologija. Reikšminiai žodžiai: žemes ūkio plėtra, inovacija, investavimas, Monte Karlo metodas, realios alternatyvos, modeliavimas. First published online: 10 Feb 2011